2020
DOI: 10.1093/sf/soaa037
|View full text |Cite
|
Sign up to set email alerts
|

Training Regimes and Skill Formation in France and Germany An Analysis of Change Between 1970 and 2010

Abstract: How do educational systems prepare workers for the labor market? Stratification research has often made a distinction between two ideal-types: “qualificational spaces,” exemplified by Germany with a focus on vocational education, and “organizational spaces,” exemplified by France with a focus on general education. However, most studies that investigated this distinction did so by focusing only on the size of the vocational sector, not on whether graduates with a vocational degree actually link strongly to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
1
10
0
2
Order By: Relevance
“…Those results imply that the differences we see between younger and older workers are being driven by career mobility. This interpretation is consistent with the findings in Elbers, Bol, and DiPrete (2021), who showed that the age differences in linkage strength in Germany are driven largely by the experiences of women. We have established so far that countries differ in their linkage strength, that these differences remain after we take account of differences in the educational and occupational distribution of countries, and that country differences in linkage strength themselves vary de-pending upon the particular educational credential of interest.…”
Section: The Heterogeneity Of Linkage Strength By Agesupporting
confidence: 92%
See 4 more Smart Citations
“…Those results imply that the differences we see between younger and older workers are being driven by career mobility. This interpretation is consistent with the findings in Elbers, Bol, and DiPrete (2021), who showed that the age differences in linkage strength in Germany are driven largely by the experiences of women. We have established so far that countries differ in their linkage strength, that these differences remain after we take account of differences in the educational and occupational distribution of countries, and that country differences in linkage strength themselves vary de-pending upon the particular educational credential of interest.…”
Section: The Heterogeneity Of Linkage Strength By Agesupporting
confidence: 92%
“…Some of the differences in effects by age are probably driven by age-specific career processes, but others may reflect historical change. Elbers, Bol, and DiPrete (2021) demonstrated considerable change in the French skill formation system over a period of 40 years but less change in the German system. To disentangle these two sources of data over the broad set of countries studied here requires further improvements in available data even though the EU LFS data have provided a considerable advance in what we know.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations